How Do Job Related Field Experiences Affect Job Readiness in Secondary Transition Students? - Uetz, Michelle (Journal of the American Academy of Special Education Professionals, 2011)
This research was conducted to determine if job related field experiences improved the confidence of secondary transition students. There were six students included in the study. The students ranged in disabilities from emotional and behavioral disability, borderline cognitive disability and severe (IQ under 60) disability. In addition, the case managers of the identified students and other transition teachers were surveyed. Students completed a survey about their ability to independently complete job seeking tasks. They then participated in field experiences to practice these skills. After practice and the opportunity to independently complete the skills, the students were asked to rate their level of independence again. The case managers of the students were asked to rate their abilities at the beginning of the study and again at the end. Transition teachers were asked to describe their observations and practices in regard to community involvement for secondary transition students. After practicing job related skills in the community students rated their ability to independently complete the tasks at a higher level than before the field experience. The case managers also rated the student ability levels higher after the experiences than before. In addition, the surveyed transition teachers reported benefits and practices in using field experiences.